THE UNITED STATES POSITION ON THE POLITICAL SYSTEMS IN UGANDA (1962-1980) (American Journal of Research in Humanities and Social Sciences, 2023)
Following the policy followed and the personalities of Milton Obote and Yedi Amin in Uganda are different, and thus created differently on the relations between Uganda and the origins of the United States, where Obote's attitude towards the cold west was recorded after participating in relying on independence, understanding the acceptances of colonial oppression, so he did not show interest in participating in relations With the United States, control of President Amin Amin is unacceptable and unhelpful for predicting a relationship. It is difficult for Uganda to function satisfactorily in the international system, and it is this behavior that remains difficult for the United States except to maintain an embassy in Kampala.